Antioxidant characteristic changes, sensory evaluation, processing and storage of functional water modified juice. (April 2023) - Wu, Tongjiao; Sakamoto, Mitsuki; Phacharapan, Santudprom; Inoue, Natsuki; Kamitani, Yoshinori
Abstract: Commercially available fruit juices modified with alkaline electrolyzed water (AlEW) and tourmaline water (TMW) were used as raw materials. The antioxidant activity, sensory evaluation, processing and storage of the modified juices were studied. The results showed that the SOD activity of the juice of the AlEW and TMW groups increased by 13% and 14%, respectively, compared with the control group. The results also showed that the total microorganism counts of the juice in the AlEW group were significantly lower than those in the TMW and the control groups at the initial storage stage (P < 0.05). Additionally, the sweet taste and overall acceptability of the juice modified with functional water was higher than that of the control group. Therefore, it was concluded that AlEW and TMW, two kinds of functional waters, could enhance the antioxidant activity, improve sweetness, maintain sourness, and improve taste of the juice. Highlights: Commercially available juice was modified with two types of functional water. Functional water increased antioxidant activity of modified juice. Functional water modification improved sweetness, maintained sourness. Functional water-modified juice had a better taste than control group.